Development of a Novel Android Controlled USB File Transfer Hub - M. Africa, Aaron Don; B. Mesina, Anna Patricia Nicole; C. Izon, Jullian Lance; N. Quitevis, Bryan Carlo (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The Universal Serial Bus (USB) is a mainstay in computer electronics and has been one of the most prominent peripherals in the world because of its portability and accessibility. On the other hand, smartphones have taken the world by storm because of the features they offer and convenience they seek to provide. This study focuses on implementing a USB hub controlled by software installed on an Android phone. Using Bluetooth technology, the phone will communicate to the hub wirelessly to perform file transfer operations. The condition which shows optimum system performance was determined through varying USB flash drives and different file sizes during testing. The tests verified different transfer rates per file for the copy & paste function. The system was also able to overwrite, rename, delete and move files. Based on the test results, the system was able to achieve at least 75% of the speed shown by the two test PCs on certain file size ranges considering the average, best and worst case transfer conditions.